Your Code Name is Jonah - Packard, Edward (New York Bantam Books, 1982)
By making the correct decisions, the reader assists the Special Intelligence Group in rescuing a marine scientist and recovering a whale song tape from the clutches of the KGB.
Include Colour Illustration
Keywords: Plot-your-own stories -- Spy stories -- Whales